2017
DOI: 10.1111/jnu.12351
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Literature on Vital Sign Assessment of Physical Activity in Primary Care

Abstract: Purpose: To conduct an integrated review of the performance and implementation of two physical activity (PA) assessment tools, the exercise vital sign (EVS) and the physical activity vital sign (PAVS), in U.S. primary care practice. Design:An integrative review following Whittemore and Knafl's methodology. Methods: Medline and the Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases were searched. Search terms were "exercise vital sign" OR "physical activity vital sign" AND "primary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…PA screening tools have been infrequently used in clinical care but they can play a role in documenting PA for monitoring and in identifying those who are not meeting PA guidelines who may benefit from an intervention ( Wald and Garber, 2018 ). Brief PA screening has been implemented in two major hospital systems in the U.S. An electronic exercise vital sign was implemented in Kaiser Permanente ( Coleman et al, 2012 ) as well as in Intermountain Healthcare ( Ball et al, 2016 ) for use in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…PA screening tools have been infrequently used in clinical care but they can play a role in documenting PA for monitoring and in identifying those who are not meeting PA guidelines who may benefit from an intervention ( Wald and Garber, 2018 ). Brief PA screening has been implemented in two major hospital systems in the U.S. An electronic exercise vital sign was implemented in Kaiser Permanente ( Coleman et al, 2012 ) as well as in Intermountain Healthcare ( Ball et al, 2016 ) for use in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, few studies have attempted to determine the validity of the EVS against device-measured estimates of PA, such as with accelerometry. 5…”
Section: Introductionmentioning
confidence: 99%
“…4 However, few studies have attempted to determine the validity of the EVS against device-measured estimates of PA, such as with accelerometry. 5 Research suggests that self-reported PA volumes may vary between ethnic groups. [6][7][8] For example, nationally representative data have shown no significant differences in accelerometer measured PA between adult non-Hispanic whites and non-Hispanic blacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its ease of use, little research is available to support this recommendation and its effect on clinical outcomes, and no prior studies have evaluated the use of a PAVS in a pediatric population. 8,20 The purpose of this study was to evaluate the use of a PAVS in a pediatric population and determine its association with common markers of cardiometabolic disease.…”
mentioning
confidence: 99%